Proses Konstruksi Pengetahuan Siswa Bertipe Belajar Visual pada Pelajaran Biologi - Aty Mulyani; Kamid Kamid; Damris Muhamad (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2013)
This study aims to reveal construction process of visual learning type student in learning biology.We employ qualitative method to disclose the subject’s learning process. The process ofknowledge construction was observed through observation, structured interview, and literaturereview. This research describes that the research subjects construct knowledge through theprocess of assimilation & accommodation. The form of knowledge construction demonstrate thatstudent’s knowledge were on the dimensions of factual knowledge, conceptual knowledge,procedural knowledge, and metacognitif knowledge. That knowledge is constructed randomlythrough disequilibrium process to equilibration.